Lupus myelopathy. Issue 1 (2nd November 2017) - Raciborska, Dominika D; Noyce, Alastair John; Pyne, Dev; Turner, Benjamin P
Abstract : Although neurological manifestations of systemic lupus erythematosus (SLE) are well recognised, myelopathy complicating SLE is rare. A 35-year-old woman presented with non-specific symptoms and a respiratory tract infection but had serological evidence of SLE. She subsequently deteriorated rapidly, developing a catastrophic spinal cord syndrome. Her initial MRI was normal; but after 1 month, her encephalopathy having progressed, repeat imaging showed characteristic myelitic changes. She responded only slowly to a combination of cyclophosphamide and corticosteroids. This case exemplifies the mixed presentations of SLE, including the under-recognised 'subpial leukomyelopathy' of central nervous system lupus. It highlights the challenges in managing lupus-related myelopathy and the benefits of a multidisciplinary approach to care.